Relationship between the physical and psychosocial conditions of postoperative gastrointestinal cancer patients and their responses to an informational material - Michiyo Mizuno; Jun Kataoka; Fumiko Oishi (Elsevier, 2017)
Objective: Postoperative patients with gastrointestinal (GI) cancer have multiple adaptation tasks and care needs to improve their quality of life (QOL). Whether their supportive care needs differ according to their physical and psychosocial conditions is unclear. This study investigated patients' (1) physical and psychosocial conditions (QOL, fatigue, anxiety, cognitive plight, and resilience) and (2) responses to an informational booklet describing cancer patients' problems and adaptation tasks, and examined the association between the two factors. Methods: A questionnaire survey was conducted to postoperative patients with GI cancer. Results: The mean age of the 69 respondents was 63 years; 59.4% of the respondents were men. Nine patients who did not read the booklet showed high fatigue and cognitive plight and low QOL. The patients (36.2%) who chose "I vaguely understood the content" showed low scores for resilience and cognitive plight while those (8.5%) who chose "I will deal with my tasks as described in the scenarios" showed high scores for both of these variables. Conclusions: The condition of some patients continued to be highly affected by their cancer. In terms of understanding the contents of the booklet, resilience was significant, and cognitive plight did not necessarily have a negative impact. The provision of information by means of a booklet might not be suitable for patients who are highly affected by their cancer. Patients may need additional support to be able to make good use of the information provided in such a booklet.